2001
DOI: 10.1152/jn.2001.86.2.935
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Counterroll Modulates the Preferred Direction of Saccade-Related Pontine Burst Neurons in the Monkey

Abstract: Saccade-related burst neurons in the paramedian pontine reticular formation (PPRF) of the head-restrained monkey provide a phasic velocity signal to extraocular motoneurons for the generation of rapid eye movements. In the superior colliculus (SC), which directly projects to the PPRF, the motor command for conjugate saccades with the head restrained in a roll position is represented in a reference frame in between oculocentric and space-fixed coordinates with a clear bias toward gravity. Here we studied the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…Another instance of the VOR is static ocular counter-rolling in response to maintained head tilt relative to gravity. Recordings from burst neurons in monkeys are compatible with torsional shift of rectus pulleys transverse to the EOM axes in the direction of ocular counterroll induced by static head tilt (Scherberger et al 2001), analogous to the coordinated torsional pulley shift observed here in convergence. In monkeys the displacement plane for 3-D eye positions during pursuit and saccades also shifts opposite to changes in head orientation relative to gravity (Hess and Angelaki 2002).…”
Section: Kinematics Of Coordinated Pulley Torsionsupporting
confidence: 66%
“…Another instance of the VOR is static ocular counter-rolling in response to maintained head tilt relative to gravity. Recordings from burst neurons in monkeys are compatible with torsional shift of rectus pulleys transverse to the EOM axes in the direction of ocular counterroll induced by static head tilt (Scherberger et al 2001), analogous to the coordinated torsional pulley shift observed here in convergence. In monkeys the displacement plane for 3-D eye positions during pursuit and saccades also shifts opposite to changes in head orientation relative to gravity (Hess and Angelaki 2002).…”
Section: Kinematics Of Coordinated Pulley Torsionsupporting
confidence: 66%
“…Previous attempts searched for such neural signals consistent with 3D ocular kinematics in the premotor pathway for generating eye movements (van Opstal et al, 1991(van Opstal et al, , 1996Hepp et al, 1993;Scherberger et al, 2001). However, here, we show that the search should not be aimed at neural pathways that implement the inverse model (i.e., those directly involved in the generation of the movement), but rather at neural pathways that implement the forward model.…”
Section: Forward Model and Eh Cellsmentioning
confidence: 60%
“…The central neural signals correlated with all types of eye movement would be expected to reflect effects of torsional reconfiguration of rectus pulleys during the VOR. Recordings from burst neurons in monkeys appear compatible with torsional shift of rectus pulleys transverse to the EOM axes induced by static head tilt [66]. In monkeys the displacement plane for 3-D eye positions during pursuit and saccades shifts opposite to changes in head orientation [67], and such shifts may be dynamic during semicircular canal stimulation [68,69].…”
Section: Implications For Neural Controlmentioning
confidence: 72%